Ezekiel 33:12-16 in Papyrus 967 - Van Rooy, H. F. (Journal for semitics, 2011)
P967 has had an important effect on the study of the Greek Ezekiel and the relationship of the original Greek to the Masoretic text. This papyrus is often seen as representing the original Greek, together with the Codex Vaticanus. The question to be answered in this paper is whether the original Greek as reconstructed by Ziegler (2006) must be adapted as a result of readings of this papyrus. A second question is whether the parallel passages in Ezekiel 18 have affected the transmission of this passage in the Septuagint. This study has indicated a number of cases where the reading of the original Greek can be reconstructed differently from Ziegler's work. In other instances, the reading of Papyrus 967 frequently supports the choice made by Ziegler on account of B and some other witnesses.